Observational Studies in Male Elite Football: A Systematic Mixed Study Review - Preciado, Maria; Anguera, M. Teresa; Olarte, Mauricio; Lapresa, Daniel (Frontiers in Psychology, 2019)
Objective: This systematic mixed study review focused on the use of observation methodology in elite men's football matches, which constitutes an innovative approach that opens up a new panorama of useful and productive research. Method: It follows the recommendations for systematic reviews and meta-analysis guidelines (PRISMA). The search was carried out in 5 databases. The articles selected and analyzed were 94 out of a total of 3,195. In order to achieve a quality assessment, the Guide has been used to inform evaluations based on observation methodology (GREOM) (Portell et al., 2013), recognized by the EQUATOR network. Results: From the methodological review analysis, information obtained indicates that 97% of the investigations used direct observation and 3% indirect observation. On the other hand, 56.5% of the articles explain the instrument used and 77% justify the applied observational design. A quantitative comparison of the proportions was made in several methodological aspects, which resulted in only 15.21% reviewing the quality of the data, and that 67.3% of the articles contribute to the mixed methods approach. The methodological review allowed to establish procedural profiles. The results indicate that 67% of the articles have been published in English, and of these, 77% have an impact factor. The majority of the researchers, 53.26%, belong to Spanish entities. The most studied substantive aspects were goal (34%), possession of the ball (28%) and corner (27%). The most observed events were Leagues, World Cups, individual players and other events. Conclusions: The results obtained refer to both substantive and methodological aspects, and allow us to configure a systematic review of mixed studies, in which we emphasize the aspects of 'systematic review' and 'mixed study', within an integrated perspective.